2015
DOI: 10.1007/s00005-015-0355-9
|View full text |Cite
|
Sign up to set email alerts
|

The Q705K and F359L Single-Nucleotide Polymorphisms of NOD-Like Receptor Signaling Pathway: Association with Chronic Pancreatitis, Pancreatic Cancer, and Periodontitis

Abstract: The aim of this study was to establish the correlation between the occurrence of Q705K and F359L polymorphisms in patients diagnosed with pancreatic diseases and periodontal conditions of various degrees of severity. The above-mentioned genetic markers were assessed in patients with pancreatic cancer (n = 18) and chronic pancreatitis (n = 39) as well as in a healthy control group (n = 115). The established inclusion criteria were the following: Caucasian descent, non-smoking, and age range 20–80, with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…One study found that the NLRP3 rs35829419 C > A (Q705K) genotype was associated with a lower survival rate in patients diagnosed with invasive colorectal cancer 49 . However, this genotype was not associated with myeloid leukemia 50 or pancreatic cancer 51 . However, the NLRP3 alleles of rs10925025 G, rs1539019 C, rs10925026 A, and rs12143966 A tended to correlate with the risk of RCC in this study.…”
Section: Discussionmentioning
confidence: 78%
“…One study found that the NLRP3 rs35829419 C > A (Q705K) genotype was associated with a lower survival rate in patients diagnosed with invasive colorectal cancer 49 . However, this genotype was not associated with myeloid leukemia 50 or pancreatic cancer 51 . However, the NLRP3 alleles of rs10925025 G, rs1539019 C, rs10925026 A, and rs12143966 A tended to correlate with the risk of RCC in this study.…”
Section: Discussionmentioning
confidence: 78%
“…Among these 12 pathways, three well-known cancer pathways were p53 signaling pathway (KEGG: rno04115), bladder cancer (KEGG: rno05219) and pathways in cancer (KEGG: rno05200). As for the other nine pathways, MAPK signaling pathway (KEGG: rno04010) [8], cell cycle pathway (KEGG: rno04110) [9], cytokine-cytokine receptor interaction pathway (KEGG: rno04060) [10], NOD-like receptor signaling pathway (KEGG: rno04621) [11], cytosolic DNA-sensing pathway (KEGG: rno04623) [12], RIG-I-like receptor signaling pathway (KEGG: rno04622) [13], Toll-like receptor signaling pathway (KEGG: rno04620) [14], chronic myeloid leukemia pathway (KEGG: rno05220) [15] and Hematopoietic cell lineage pathway (KEGG: rno04640) [16] were also reported to be associated to cancers in the previous studies. To confirm the results from the microarray data analysis, the expression levels of six out of the total 21 DE genes ( Figure 2 ) in pathways in cancer (KEGG: rno05200) were measured using the qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…Among these 12 pathways (Table 1 ), three well-known cancer pathways were p53 signaling pathway (KEGG: rno04115), bladder cancer (KEGG: rno05219) and pathways in cancer (KEGG: rno05200). As for the other nine pathways, MAPK signaling pathway (KEGG: rno04010) [ 9 ], cell cycle pathway (KEGG: rno04110) [ 10 ], cytokine-cytokine receptor interaction pathway (KEGG: rno04060) [ 11 ], NOD-like receptor signaling pathway (KEGG: rno04621) [ 12 ], cytosolic DNA-sensing pathway (KEGG: rno04623) [ 13 ], RIG-I-like receptor signaling pathway (KEGG: rno04622) [ 14 ], Toll-like receptor signaling pathway (KEGG: rno04620) [ 15 ], chronic myeloid leukemia pathway (KEGG: rno05220) [ 16 ] and Hematopoietic cell lineage pathway (KEGG: rno04640) [ 17 ] had also been associated to cancers in previous studies. Among the total 73 genes involved in 12 enriched pathways, 56 and 17 were up- and down-regulated, respectively ( Supplementary Table 3 ).…”
Section: Resultsmentioning
confidence: 99%